The small RNA microRNA-212 regulates sirtuin 2 expression in a cellular model of oxygen-glucose deprivation. Issue 17 (10th December 2019) - Zhao, Guangming; He, Juan; Wang, Zhiguang; Bao, Leri; Cong, Ribo; An, Wenrui; Zhao, Xueliang; Liu, Guiying
Abstract : MicroRNA-212 has been found to play an important role in several types of diseases, but the functional and potential mechanisms of microRNA-212 in ischemic brain injury are still unclear. The aims of this study were to investigate the potential role of microRNA-212 in ischemic brain injury and to reveal potential molecular mechanisms. The rat oxygen-glucose deprivation and simulated reperfusion model was established to study the role of microRNA-212 in ischemic brain injury. The expression of microRNA-212 in oxygen-glucose deprivation and simulated reperfusion model and its effect on cell proliferation were measured by quantitative reverse transcription PCR and Cell Counting Kit-8 assay, respectively. The relationships between microRNA-212 and sirtuin 2 were confirmed by luciferase-reporter assay. We observed that microRNA-212 was downregulated after oxygen-glucose deprivation and simulated reperfusion treatment. Besides, the cells viabilities were increased/decreased in oxygen-glucose deprivation and simulated reperfusion model after transfection with microRNA-212 agomir (agonist of microRNA-212 action) and microRNA-212 antagomir (inhibitor of microRNA-212 action). In addition, luciferase and western blot experiments showed that microRNA-212 directly regulated sirtuin 2 changes. Furthermore, promotion of neuronal survival by microRNA-212 was blocked by overexpression of sirtuin 2, whereas the neuronal death induced by microRNA-212 inhibition was rescued by sirtuin 2 inhibition. Taken together, our study revealed that the role of miR-212 in the modulation of ischemic brain injury might be achieved by regulating sirtuin 2, which provides potential biomarkers and candidates for the treatment of cerebral ischemia.